2021 AHA/ACC/ASE/CHEST/SAEM/SCCT/SCMR Guideline for the Evaluation and Diagnosis of Chest Pain: Executive Summary: A Report of the American College of Cardiology/American Heart Association Joint Committee on Clinical Practice Guidelines. Issue 22 (28th October 2021) - Gulati, Martha; Levy, Phillip D.; Mukherjee, Debabrata; Amsterdam, Ezra; Bhatt, Deepak L.; Birtcher, Kim K.; Blankstein, Ron; Boyd, Jack; Bullock-Palmer, Renee P.; Conejo, Theresa; Diercks, Deborah B.; Gentile, Federico; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Aim: This executive summary of the clinical practice guideline for the evaluation and diagnosis of chest pain provides recommendations and algorithms for clinicians to assess and diagnose chest pain in adult patients. Methods: A comprehensive literature search was conducted from November 11, 2017, to May 1, 2020, encompassing studies, reviews, and other evidence conducted on human subjects that were published in English from PubMed, EMBASE, the Cochrane Collaboration, Agency for Healthcare Research and Quality reports, and other relevant databases. Additional relevant studies, published through April 2021, were also considered. Structure: Chest pain is a frequent cause for emergency department visits in the United States. The "2021 AHA/ACC/ASE/CHEST/SAEM/SCCT/SCMR Guideline for the Evaluation and Diagnosis of Chest Pain" provides recommendations based on contemporary evidence on the assessment and evaluation of chest pain. These guidelines present an evidence-based approach to risk stratification and the diagnostic workup for the evaluation of chest pain. Cost-value considerations in diagnostic testing have been incorporated and shared decision-making with patients is recommended.